Closing Water Cycles in the Built Environment through Nature-Based Solutions: The Contribution of Vertical Greening Systems and Green Roofs - Pearlmutter, David (2021)
Water in the city is typically exploited in a linear process, in which most of it is polluted, treated, and discharged; during this process, valuable nutrients are lost in the treatment process instead of being cycled back and used in urban agriculture or green space. The purpose of this paper is to advance a new paradigm to close water cycles in cities via the implementation of naturebased solutions units (NBS_u), with a particular focus on building greening elements, such as green roofs (GRs) and vertical greening systems (VGS). The hypothesis is that such “circular systems” can provide substantial ecosystem services and minimize environmental degradation. Our method is twofold: we first examine these systems from a life-cycle point of view, assessing not only the inputs of conventional and alternative materials, but the ongoing input of water that is required for irrigation. Secondly, the evapotranspiration performance of VGS in Copenhagen, Berlin, Lisbon, Rome, Istanbul, and Tel Aviv, cities with different climatic, architectural, and sociocultural contexts have been simulated using a verticalized ET0 approach, assessing rainwater runoff and greywater as irrigation resources. The water cycling performance of VGS in the mentioned cities would be sufficient at recycling 44% (Lisbon) to 100% (Berlin, Istanbul) of all accruing rainwater roof–runoff, if water shortages in dry months are bridged by greywater. Then, 27–53% of the greywater accruing in a building could be managed on its greened surface. In conclusion, we address the gaps in the current knowledge and policies identified in the different stages of analyses, such as the lack of comprehensive life cycle assessment studies that quantify the complete “water footprint” of building greening systems.